Growth of magnetotactic sulfate‐reducing bacteria in oxygen concentration gradient medium. Issue 6 (December 2016) - Lefèvre, Christopher T.; Howse, Paul A.; Schmidt, Marian L.; Sabaty, Monique; Menguy, Nicolas; Luther, George W.; Bazylinski, Dennis A.
Summary: Although dissimilatory sulfate‐reducing bacteria (SRB) are generally described as strictly anaerobic organisms with regard to growth, several reports have shown that some SRB, particularly Desulfovibrio species, are quite resistant to O2 . For example, SRB remain viable in many aerobic environments while some even reduce O2 to H2 O. However, reproducible aerobic growth of SRB has not been unequivocally documented. Desulfovibrio magneticus is a SRB that is also a magnetotactic bacterium (MTB). MTB biomineralize magnetosomes which are intracellular, membrane‐bounded, magnetic iron mineral crystals. The ability of D. magneticus to grow aerobically in several different media under air where an O2 concentration gradient formed, or under O2 ‐free N2 gas was tested. Under air, cells grew as a microaerophilic band of cells at the oxic–anoxic interface in media lacking sulfate. These results show that D. magneticus is capable of aerobic growth with O2 as a terminal electron acceptor. This is the first report of consistent, reproducible aerobic growth of SRB. This finding is critical in determining important ecological roles SRB play in the environment. Interestingly, the crystal structure of the magnetite crystals of D. magneticus grown under microaerobic conditions showed significant differences compared with those produced anaerobically providing more evidence that environmental parameters influence magnetosome formation.